A qualitative exploration of the perceptions of professional registration by Australian paramedics during the transition into professional regulation. (December 2022) - Reed, Buck; Cowin, Leanne; O'Meara, Peter; Wilson, Ian
In 2018, Australian paramedics entered the National Registration and Accreditation Scheme for Health Practitioners. The scheme represented a significant change in the way paramedics were regulated and able to self-identify. Equally, it brought substantial changes to the individual accountability and responsibilities of practitioners. Response to these reforms was largely positive; however, diverse views existed on the intent and impacts of the scheme. Paramedics were surveyed immediately before registration commencement to examine their views concerning the new regulatory framework. Supportive views included acknowledgement of regulation's public safety function and potential advancement of the profession. Dissenting views predicted increased practitioner risk and degradation of working conditions. Importantly, this study explores how members of the same profession can have diverse views of the same regulatory scheme. This study supports the notion that paramedicine consists of diverse subcultures with differing worldviews. This presents challenges in ensuring cohesive professional engagement with regulation and the evolution of the profession.